Effects of Conduction Velocity and Spectral Comperssion on Fractal Parameters of Myoelectric Signals - Talebinejad, Mehran; Chan, Adrian D.C.; Miri, Ali (CMBES Proceedings, 2007)
Myoelectric signals undergo spectral compression during muscle fatigue, which is largely due to an underlying mechanism of decreasing muscle fiber conduction velocity. To examine the effects of spectral compression and changes of the conduction velocity on the fractal parameters of the myoelectric signals, we evaluate fractal indicators extracted from the power spectrum in this context. In this study, the myoelectric signals are simulated using a structural model. Fractal indicators are computed using a novel general power spectrum method. We have previously showed that these indicators are capable of sensing force and joint angle independently. These experimental results show fractal indicators provide measures independent from spectral compression, further demonstrating the potential of this form of myoelectric fractal analysis.